Lung function in patients with primary ciliary dyskinesia: an iPCD Cohort study. Issue 2 (23rd August 2018) - Halbeisen, Florian S.; Goutaki, Myrofora; Spycher, Ben D.; Amirav, Israel; Behan, Laura; Boon, Mieke; Hogg, Claire; Casaulta, Carmen; Crowley, Suzanne; Haarman, Eric G.; Karadag, Bulent; Koerner-Rettberg, Cordula; et al.
Primary ciliary dyskinesia (PCD) has been considered a relatively mild disease, especially compared to cystic fibrosis (CF), but studies on lung function in PCD patients have been few and small. This study compared lung function from spirometry of PCD patients to normal reference values and to published data from CF patients. We calculated z-scores and % predicted values for forced expiratory volume in 1 s (FEV1 ) and forced vital capacity (FVC) using the Global Lung Function Initiative 2012 values for 991 patients from the international PCD Cohort. We then assessed associations with age, sex, country, diagnostic certainty, organ laterality, body mass index and age at diagnosis in linear regression models. Lung function in PCD patients was reduced compared to reference values in both sexes and all age groups. Children aged 6–9 years had the smallest impairment (FEV1 z-score −0.84 (−1.03 to −0.65), FVC z-score −0.31 (−0.51 to −0.11)). Compared to CF patients, FEV1 was similarly reduced in children (age 6–9 years PCD 91% (88–93%); CF 90% (88–91%)), but less impaired in young adults (age 18–21 years PCD 79% (76–82%); CF 66% (65–68%)). The results suggest that PCD affects lung function from early in life, which emphasises the importance of early standardised care for all patients. PCD affects lung function from an early age, similarly to CF, thus early multidisciplinary management is crucial http://ow.ly/T9ch30kHXns